Imitating the Egyptian Hieroglyphic Script in the Roman Era: The Case from Potaissa (Dacia Porolissensis) - Deac, Dan-Augustin (Zeitschrift für ägyptische Sprache und Altertumskunde, 2014)
The present paper studies a unique monument discovered in 1979 by the Romanian researcher Nicolae Vlassa. Unfortunately due to his sudden pass-away, the stela/obelisk remained hidden from the scientific community until now. Although it is a stray discovery and not from an archaeological context, the author, with the help of geo-petrographical analysis, tries to “remove the dust” of this monument, putting it in the proper place, namely in the corpus of the aegyptiaca finds coming from the Roman province of Dacia Porolissensis.